Internacionalizacija doma in internacionalizacija kurikula v visokem šolstvu - konceptualne razmejitve in implementacija v praksi - Aškerc Zadravec, Katarina (Sodobna pedagogika, 2025)
Globalization, internationalization, and other dynamic factors of modern world demand the development of graduates who are well-equipped to function successfully in a multicultural and rapidly changing world. It is crucial for higher education institutions to respond effectively to the needs of a global, multicultural environment by systematically and holistically integrating international and intercultural dimensions into their study programs. This is addressed through the concepts of internationalisation at home and the internationalisation of the curriculum. In this article, theoretical foundations of these concepts are presented and justified, beginning with the theoretical definition of the internationalisation of higher education and focusing on the key aspects of this process, with particular emphasis on the motivations and approaches for introducing an internationalised curriculum into the study process. Concrete examples of the implementation of an internationalised curriculum are provided based on the theory of constructive alignment, which is concluded with a critical discussion on the challenges faced in the practical implementation of an internationalised curriculum.
Keywords: internacionalizacija; kurikulum; visokošolski študij